The Changing Geography of Banking and Finance The Main Issues - Zazzaro, Alberto; Fratianni, Michele; Alessandrini, Pietro; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Two contrasting trends have emerged from the intense integration and consolidation process that have swept the European and U.S. banking industry in the 1990s: the geographical diffusion of banking structures and instruments and the geographical concentration of banking power in a few financial centers within each country. The first trend has contributed to greatly reduce the operational distance that separates banks from their clientele. The second has increased the functional distance that separates the bank's decision center from its operational branches. The conflicting movements in operational and functional distances have left a mark on market structure, financial integration and regulation of the banking industry, and have induced a transformation in organizational structures, lending behavior and relationships between banks and firms. This book, not only surveys the great research effort that has been made recently on the geography of banking and finance, but also provides new insights and empirical evidence on how the geography of banking and finance has evolved and impacted its customers. This is a timely and valuable volume that collects up-to-date empirical research on the geography of the banking industry and financial centers. Allen N. Berger H. Montague Osteen, Jr. Professor in Banking and Finance Moore School of Business University of South Carolina, USA The geography of banking has changed dramatically in recent years, under the combined effect of new information technology, deregulation and international integration. This book assesses thoroughly what we know and what we don't know yet about this process and about its effects on the provision of credit to households and firms (especially small and medium ones). It is going to be a valuable reference on the evolution of the banking industry for years to come. Marco Pagano Professor of Economics University of Naples Federico II, Italy The subdiscipline concerned with the geography of banking is a relatively new one, and the research frontier is still largely unexplored. This book makes a timely and valuable contribution to opening up this territory; providing intriguing insight into how new information technologies, financial innovation, de- and re-regulation, and globalisation processes more generally, are reshaping not only the geographies of banking itself, but also the spatialities of credit provision, financial flows and monetary circulation. An essential read for financial economists, economic geographers and all those interested in the world of finance. Ron Martin Professor of Economic Geography University of Cambridge, UK
Distance and Banks' Organization -- The Changing Geography of Banking and Finance: The Main Issues -- Financial Innovation, Organizations, and Small Business Lending -- Does Distance Matter in Banking? -- Distance, Bank Organizational Structure, and Lending Decisions -- Geographical Organization of Banking Systems and Innovation Diffusion -- Distance and Internet Banking -- Borders and Market Structure -- Bank Market Structure, Competition, and Stability: Issues and Concepts -- Bank Cross-Border Mergers and Acquisitions: Causes, Consequences, and Recent Trends -- What Are Borders Made of? An Analysis of Barriers to European Banking Integration -- Regulatory Framework and Financial Centers -- Designing a Regulatory and Supervisory Framework for Integrated Financial Markets -- Crisis Management and Lender of Last Resort in the European Banking Market -- The Evolutionary Chain of International Financial Centers -- Financial Centers Between Centralization and Virtualization.
Keywords: ECONOMICS; ECONOMIC POLICY; FINANCE; ENTREPRENEURSHIP; ECONOMICS/MANAGEMENT SCIENCE; FINANCE/INVESTMENT/BANKING.; FINANCIAL ECONOMICS; ECONOMIC POLICY; ENTREPRENEURSHIP